THE PARABLE OF THE PRODIGAL AND HIS BROTHER: LITERARY AND HISTORY CHRITICISM FROM LUKE 15:11-32 - Gabrelia Astrid Melatunan (Bethel Press, 2022)
The parable of the prodigal son in Luke 15:11-32 is a passage that is often discussed. The discussion is usually directed to the youngest who realizes his mistake and then returns to his father. The response of the father who hugged the youngest back from his escape drew anger from the eldest. After the story, the reader will close it and take the implications that can be learned from the parable. However, there is another aspect that deserves to be studied, especially regarding the deepest meaning of the parable. This study aims to explain the meaning of the parable of the prodigal son. The research method used is biblical literary and history criticism. The results showed that the meaning of the prodigal son was not only directed to the youngest. But to the eldest who does not understand his father's heart towards those who return from his loss. Thus, what is missing in this parable is the eldest, not the youngest.